The state and public policies to tackle hunger in Brazil O estado e as políticas Públicas de combate à fome no Brasil - da Silva Cruz, Jean [UNESP]; de Medeiros Hespanhol, Rosangela Aparecida [UNESP] (Elsevier, 2025)
The phenomenon of hunger and its permanent state in Brazil may be considered one of the direst of all social disasters today. That being the case, this article seeks to discuss the role of the Brazilian State in public policymaking, particularly regarding the fight against hunger and, especially, the issue of food security. In order to achieve this objective, the following procedures are applied: a) a survey of the specialized literature to enable the design of a conceptual and exploratory theoretical framework; and b) first- and second-hand document analysis. The procedural and historical linkages of food and nutrition policies and programs as a public and/or political intervention matter are characterized by a fragmented and/or discontinued approach. Equally, they have been aggravated by advances in cycles of neoliberal policies in government agendas in the period 2016–2022, which signal a political-ideological agenda of dismantling public policy.